CCR-CCL axes as key upstream influencers of pancreatic ductal adenocarcinoma: CCR2–CCL2, CCR5–CCL5, CCR4–CCL17/22, CCR6–CCL20, CCR7–CCL19/21 - Bahng, Ingyu (Frontiers in Immunology, 2026)
PDAC remains one of the most lethal malignancies, characterized by a highly desmoplastic ECM that promotes an immunosuppressive signaling network and dampens the effectiveness of traditional therapies. Among the several key contributors to its immune evasion pathways are chemokine signaling axes, which orchestrate the recruitment of regulatory immune cell populations, promote metastasis, and remodel the TME in favor of tumor progression. This review comprehensively examines the roles of major CCR-CCL signaling pathways—primarily focusing on the CCR2–CCL2, CCR5–CCL5, CCR4–CCL17/22, CCR6–CCL20, and CCR7–CCL19/21 axes—in PDAC development, detailing their expression patterns, immunologic impact, and downstream signaling mechanisms and outcomes. We further detail past and ongoing therapeutic efforts and trials addressing these axes in both PDAC and relevant non-PDAC settings via several small-molecule antagonists and monoclonal antibodies: BMS-813160, Maraviroc, Leronlimab, FLX475, PF-07054894, IDOR- 1117-2520, and CAP-100. Despite continuous advances in the field, the current body of evidence remains limited and presents significant research gaps in areas such as spatial profiling, stage-specific analyses, and general mechanistic validation in PDAC-specific settings. Addressing these shortcomings will be key to developing a more comprehensive knowledge of the field and improving future therapeutic strategies to overcome PDAC.